Editorial: Community Adaptation to Photobiomodulation Near-Infrared Based on Post-Partum Culture Care - Rosnani Rosnani (Universitas Airlangga, 2021)
Editorial: Community Adaptation to Photobiomodulation Near-Infrared Based on Post-Partum Culture Care